Electrophysiological Measures of Auditory Processing in Patients with Multiple Sclerosis - Folmer, Robert L.; Hutter, Michele M.; Lilly, David J.; Shannon, Jeffrey; Casiana, Linda; Wilmington, Debra; Lewis, M. Samantha; Billings, Curtis J.; Krisky, Christine; Berlow, Yosef A.; Pollaro, James; Rooney, William; Bourdette, Dennis (Seminars in Hearing, 2012)
Previous studies demonstrated that patients with multiple sclerosis (MS) experience more hearing loss than age-matched control subjects. Patients with MS also exhibit deficits processing auditory stimuli, including speech in a background of noise. These findings suggest that auditory deficits in the MS population can result from damage to central neural pathways in addition to peripheral hearing structures. To assess auditory processing functions in patients with MS, this study used auditory event-related potentials (AERPs)—specifically, the auditory brain stem response (ABR) and long-latency AERPs including the P300. AERPs recorded from 20 patients with MS were compared to AERPs from 20 healthy control subjects. When ABR stimuli (clicks) were presented monaurally, there were no significant differences between groups in component latencies or amplitudes for waves I through V. However, binaural presentation of the same stimuli elicited wave V ABR components significantly greater in amplitude for the control group compared with the MS group. Long-latency AERP results showed no significant differences between groups for N100 latency and amplitude or for P300 latency. P300 component amplitude was significantly greater for control subjects compared with patients with MS. It is probable that neural degeneration and impaired neural transmission within the MS group contributed to these AERP results. AERPs are useful tools that can be used to assess peripheral and central auditory functions as well as cognitive processing abilities in patients with MS. AERPs could be used to evaluate neural integrity, disease progression, and treatment efficacy in this population.
Keywords: multiple sclerosis; MS; auditory event-related potentials; evoked potentials; AERP